The role of academic procrastination in the occurrence of depression, anxiety, and stress among college students - Lawrence Anthony U. Dollente; Armand G. Aton; Jomar B. Esto; Ashley Coleen S. Ortiz; Mary Jane B. Castilla; Eimer M. Estilloso; Girlie D. Batapa; Ruben L. Tagare, Jr.; Lara Ivanah C. Nadela; Paul John B. Ongcoy; Donnie M. Tulud; Vibekehh N. D. Bat-og; Altair V. Neri; Maybell S. Martin; Gideon S. Sumayo (International Journal of Evaluation and Research in Education (IJERE), 2026)
Despite growing attention to academic procrastination and student mental health, few studies have examined how procrastination is linked specifically to depression, anxiety, and stress (DAS) among college students in the Southern Philippines—an underrepresented context in the literature. Anchored in the cognitive-behavioral theory, which posits that maladaptive behaviors like procrastination can reinforce negative emotional states, this study investigates the relationship between academic procrastination and psychological distress. Using a quantitative descriptive-correlational design, data were gathered from 796 college students selected through simple random sampling. Instruments included the academic procrastination scale and the DASS-21, both with strong reliability indices. Descriptive statistics were used to identify the severity levels of procrastination and mental health symptoms, while Pearson’s correlation coefficient examined their relationships. Most of students demonstrated moderate levels of academic procrastination. Notably, while depression was significantly correlated with procrastination, anxiety and stress showed no significant association. This suggests that procrastination may particularly intensify depressive tendencies, such as low motivation and self-worth, rather than general stress or anxiety. The high prevalence of extremely severe anxiety and moderate to severe stress signals broader psychosocial challenges among students that may not be directly linked to procrastination but still demand attention. These findings contribute to the academic discourse by contextualizing mental health and behavioral patterns in a regional student population. The study has practical implications for curriculum planners, mental health professionals, and institutional policymakers, particularly in designing support systems that address the psychological and behavioral needs of students within culturally specific frameworks.